Securing Crop Genetic Diversity: Reconciling EU Seed Legislation and Biodiversity Treaties. Issue 3 (November 2016) - Prip, Christian; Fauchald, Ole Kristian
Abstract : In May 2015, the European Commission withdrew its proposal for a new Regulation on Plant Reproductive Material. For decades, the European Union (EU) has struggled to strike a balance between seed legislation and the rights of farmers to save and exchange seed. The shelving of the draft Regulation was a major setback, given the need for legislative action in the aftermath of the Kokopelli judgment of the Court of Justice of the EU. This article discusses EU seed legislation in light of the Convention on Biological Diversity and the International Treaty on Plant Genetic Resources for Food and Agriculture. It analyses possible options and dilemmas for Norway in reconciling commitments to promote effective and high‐quality food production in a well‐functioning market, and securing long‐term crop genetic diversity. Norway's association with the internal market through the European Economic Area Agreement, as well as the fact that the Norwegian seed market is small and of scant interest to major seed companies, indicate that Norway enjoys flexibility in policy design. The article finds that EU seed legislation does not allow effective regimes for exchange and use of conservation varieties, possibly at odds with the two treaties and the principles of subsidiarity and proportionality .